2016
DOI: 10.1186/s12872-016-0241-3
|View full text |Cite
|
Sign up to set email alerts
|

Unmet need in the hyperlipidaemia population with high risk of cardiovascular disease: a targeted literature review of observational studies

Abstract: BackgroundThe aim of this study was to examine recommended target levels of low-density lipoprotein cholesterol (LDL-C) for hyperlipidaemia patients at high risk (i.e., with two or more risk factors or coronary heart disease or its risk equivalents) for cardiovascular disease (CVD); to determine LDL-C targets recommended by guidelines, and to examine the proportions of patients who do not achieve targeted LDL-C levels in real-world studies.MethodsElectronic databases were searched: Medline, Medline In-Process,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…Previous studies showed that an achievement of recommended LDL-C goal is associated with decreased risk of future CV events among patients with established CVD [7,8]. Despite the benefit of LDL-C goal achievement, the current management of LDL-C in actual clinical settings is suboptimal, leading to the elevated risk of CV events among patients with dyslipidemia [9,10]. Unfortunately, there is a paucity of evidence for current status of LDL-C goal achievement among broad population with various CV risk levels in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that an achievement of recommended LDL-C goal is associated with decreased risk of future CV events among patients with established CVD [7,8]. Despite the benefit of LDL-C goal achievement, the current management of LDL-C in actual clinical settings is suboptimal, leading to the elevated risk of CV events among patients with dyslipidemia [9,10]. Unfortunately, there is a paucity of evidence for current status of LDL-C goal achievement among broad population with various CV risk levels in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Se define como un aumento de la concentración de lípidos en sangre [1]. Estos lípidos circulan unidos a proteínas, denominándose lipoproteínas, entre las que encontramos las lipoproteínas de baja densidad (LDL), las cuales son susceptibles de sufrir modificaciones como la oxidación dando lugar a las LDL oxidadas (OxLDL) [2,3]. Estas OxLDL están implicadas en procesos inflamatorios, disfunción endotelial y remodelación de la matriz extracelular (MEC) [4].…”
Section: Introductionunclassified
“…[2][3][4] Despite the widespread availability of effective lipid-lowering agents, such as statins, a significant proportion of patients at high risk of ASCVD continue to be managed suboptimally due to insufficient therapeutic efficacy, safety concerns regarding higher doses of statins, and poor compliance. 5,6 Therefore, there is a medical need for additional lipid-lowering options capable of minimizing the residual cardiovascular risk of patients who display a suboptimal response and/or intolerance to current first-line agents. 7 Bococizumab is a humanized monoclonal antibody against proprotein convertase subtilisin/kexin type 9 (PCSK9), [8][9][10][11][12][13][14][15][16][17] which is a protein that regulates the availability of the LDL receptor (LDLR) expressed predominantly on hepatocytes.…”
Section: Introductionmentioning
confidence: 99%